Informal Economies: Development Reasons in the Mirror of the World Experience - БарсуковаСветлана Юрьевна (Journal of Economic Sociology, 2010)
The paper analyzes the reasons of the informal economies’ growth in the developed and developing countries. Classic determinants of informal economy like economicbackwardness of the country,migration flows, specificity of the professional and socio-demographic characteristics of the population, economic expansion of the cheap goods from the third countries, increase of sub-contracting relations, fight with trade unions and etc., are discussed here. These reasons are given as hypothesizes, which are verified empirically in the paper. The main conclusion of the paper is that every hypothesis is true for particular country, industry and time period. However none of the hypothesis is universal. Informal economies vary greatly among the countries, that is why there is no grounds to speak about unique system of reasons of the informal economy without national country specifics.